Produktivitas Masyarakat Dengan Memanfaatkan Sumber Daya Lokal (Studi Kasus Masyarakat Desa Wanagora Kulon, Rembang, Purbalingga) (Kampelmas, 2022)
Produktivity is an activity to process or produce something. Every human being can certainly carry out productive activities, one of which is by utilizing existing resources. This study aims to see how far the productivity of the community by utilizing local resources, especially the people of Wanogara Kulon Vilage, Rembang, Purbalingga. This research was conducted during the Community Service Program (KKN) in 2022. Local resources owned by Wanogara Kulon Village, Rembang, Purbalingga can increase creativity and the ecomony of rural communities.